Examining the Appeal of Quality Service: A Study on the Impact of Product Quality on Purchase Decisions at Hani Salon - Agnes Pebriani; Ratih Amelia; Tyus Windi Ayuni; Tina Linda; Ahmad Rivai (Yayasan Bina Bisnis Nusantara Medan, 2025)
Purchase decision-making is a critical aspect of consumer behavior that involves evaluating the quality of products or services offered. This study aims to analyze the influence of product quality on consumer purchase decisions at Hani Salon, a beauty salon located in Medan, Indonesia. As product variety increases in the market, consumers have become more selective, prioritizing service quality in their choices. A quantitative research approach was employed, with data collected through questionnaires and interviews. The findings reveal that product quality has a positive and significant impact on purchase decisions, with a coefficient of determination (R²) of 90.2%. These results suggest that enhancing product quality at Hani Salon can significantly drive consumer purchase decisions and offer strategic insights for improving customer satisfaction and loyalty.